The role of cardiac dysfunction in multiorgan dysfunction. Issue 2 (April 2016) - Donati, Abele; Carsetti, Andrea; Damiani, Elisa
Abstract : Purpose of review: The aim of this review was to examine the main determinants of cardiac dysfunction in critically ill patients, as well as how a reduction in cardiac performance influences other organ function. Recent findings: Cardiac dysfunction is a frequent complication in critically ill patients and contributes to organ hypoperfusion and poor outcome. Pathophysiological determinants may include a primary ischaemia/reperfusion injury of the heart, effects of systemic inflammatory and adrenergic responses of the body to a variety of acute insults, as well as cardiovascular effects of commonly applied intensive respiratory or haemodynamic treatments. A strict connection exists between cardiac and other organ function, mediated by haemodynamic, humoral, and immune mechanisms. Heart, lungs, kidneys, and other splanchnic organs such as gut and liver influence each other function in a bidirectional way: this organ crosstalk must be regarded as a key aspect in multiorgan dysfunction. Summary: The heart should never be regarded as an isolated organ. When dealing with cardiac dysfunction, clinicians must consider the underlying pathophysiology, potential myocardial depressant effects of intensive treatments, and the complex interaction with other organ function.